Axial wall angulation for rotational resistance in a theoretical‐maxillary premolar model - John F. Bowley; Po Lee; Wen‐Fu Thomas Lai (Wiley, 2019)
Abstract Objectives The aim of this study was to determine the influence of short base lengths and supplemental grooves on surface area and rotational resistance in a simulated‐maxillary premolar. Materials and Methods Trigonometric calculations were done to determine the total surface area with and without supplemental grooves. Additional computations were done to determine the maximum wall angle needed to resist rotation displacement in a premolar‐sized model. Wall heights of 3.0, 4.0, and 5.0 mm were used in the surface area and rotational axis computations. The rotational axis was located on the lingual restoration margin to produce a buccal‐to‐lingual rotational displacement. Results Total surface area decreased with increasing four‐wall taper levels from 2° to 18° and decreasing preparation heights from 5 to 3 mm. Significant surface area improvements were found with the supplemental use of mesial and distal axial grooves compared with the same condition without grooves in all taper levels and preparation height categories. Resistance to rotational displacement was determined to occur at only at very low levels of opposing wall taper angles. The use of supplemental grooves on mesial and distal axial walls significantly improved both total surface area and rotational resistance. Conclusions The vertical wall taper angles, preparation heights, and supplemental grooves play a role in resistance form and restoration stability.